Verbal processes in media discourse: frequency and organization of the message - Cabral, Sara Regina Scotta (2012)
The main aim of the SAL (Systemics Across Languages) Project is to Investigate the use of verbal processes in some different types of discourse. This paper analyzes the use of five verbs, in Brazilian newspapers: dizer, afirmar, informar, pedir e anunciar (say, affirm, inform, ask and announce, inform, ask and announce). Used in verbal clauses, especially in those with statements from external sources, these verbs have the role of introducing the discourse of another as a way to confer authority to the journalists’ statements. The analysis focus on three aspects: the type of Sayer, the mood of the clauses and the organization of the message. By using the computer program WordSmith Tools (SCOTT, 2008), the data were quantified from a set of 656 news collected from Folha de São Paulo and London BBC in 2009. The results point to the existence of three main patterns used by journalists concerning the five verbs analyzed. Other particularities are: a) Sayers that usually represent official sources, what is done by nouns, pronouns or noun groups in which the modifier indicates the position held; b) predominance of the indicative mood and the simple past tense, especially in the third person singular; c) a balance between quoting and projection, that one generally before the verbal process.